Modelo de un sistema de inteligencia de negocios basado en S-BSC para entidades prestadoras de servicio de salud de alta complejidad sin ánimo de lucro (2015)
This state of knowledge aims to conduct a literature review of relevant concepts related to the implementation of Balanced Scorecard in organizations. The relevant Balanced Scorecard concepts will be addressed from the four perspectives that must be taken into account for its implementation: Clients, Financial, Internal Processes, Innovation and learning. The advantages of the implementation of BSC and what it represents for organizations at the strategic level, of the indicators that measure the achievement of its objectives and how it all translates into the transformation of its strategic vision. This theoretical framework is part of the development of master's thesis: Model of a business intelligence system based on S-BSC for non-profit high complexity health service providers; Therefore, in this theoretical framework, the additional concepts to which the Balanced Scorecard of sustainability refers, economic, social and environmental aspects, that a healthcare provider must address as its raison d'être will be addressed. Different considerations will be exposed in the implementation of the BSC model in entities providing health services of high complexity (hereinafter EPSSAC) derived from the research carried out, as well as some results generated from the adoption of this model in health organizations.